Health Care Quality and Spending: A Quantitative Study of Five Nations During Covid-19 - Andreea BREAZU (Communications of International Proceedings, 2022)
Healthcare is a broad concept that refers to the different systems on which we rely to preserve our health by treating (or preventing) illness, injury, disease, and other physical or mental disabilities. Each country has its own health system, which provides a variety of healthcare services to its population. Furthermore, various international organizations have proposed several methods for measuring the quality of these health services to identify how effective existing systems operate, to allow comparisons between entities that encourage shared learning, to allow evaluations of change over time, and to increase transparency. This quantitative study examines five nations' health indicators: Spain, Italy, Greece, Poland, and Hungary. Research indicators include current health spending as a proportion of GDP, healthcare resources, and four variables that assess the quality of healthcare between 2019-2021. Data was collected from the OECD database and, according to statistics, Spain devoted the largest proportion of GDP to health from 2019 to 2022, and 81.5% of Spanish women received a mammographic examination in the past two years.
Keywords: Covid-19; GDP; healthcare spending; performance indicators; quality of the medical system.